1992
DOI: 10.1002/ijc.2910510524
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene‐glycol‐modified interleukin‐2 is superior to interleukin‐2 in locoregional immunotherapy of established guinea‐pig tumors

Abstract: Polyethylene glycol-modified recombinant human interleukin-2 (PEG-IL-2) represents a cytokine with prolonged circulatory half-life and increased antitumor activity as compared to recombinant interleukin-2 (rIL-2) after systemic administration. We studied whether PEG-IL-2 would also be advantageous in locoregional immunotherapy using a syngeneic tumor model. Intradermal inoculation of line-10 tumor cells into the flanks of strain-2 guinea-pigs results in a fast-growing tumor and regional lymph-node metastases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Finally, it should be noted that IL2-containing IC are only one method of providing enhanced IL2-related effects. IT injection of liposomal IL2 or polyethylene glycol-modified recombinant IL2 have both been shown to induce significant antitumor effects against both primary and distant non-injected tumors in animal models [27,31]. Comparison of IL2-containing IC to other methods of increasing the delivery of IL2 are indicated to understand the relative efficacy and toxicities related to these modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it should be noted that IL2-containing IC are only one method of providing enhanced IL2-related effects. IT injection of liposomal IL2 or polyethylene glycol-modified recombinant IL2 have both been shown to induce significant antitumor effects against both primary and distant non-injected tumors in animal models [27,31]. Comparison of IL2-containing IC to other methods of increasing the delivery of IL2 are indicated to understand the relative efficacy and toxicities related to these modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Again, even in the absence of mature T cells, IT hu14.18-IL2 resulted in significant antitumor effects (p = 0.04 for IT IC vs. IT PBS, days [22][23][24][25][26][27][28]. IC treatment also resulted in a significant survival advantage where 3 of 5 IC-treated mice were still alive on day 79, while PBS-treated mice required euthanasia between days 22-40 due to large tumor burden (data not shown, p <0.0018, day 79).…”
Section: Effective It Response In the Absence Of T Cellsmentioning
confidence: 99%
“…exogenous IL-2 to produce cytokines and to recruit Partial responses were also described in HNSCC paspecific and nonspecific immune effector mechanisms dents using combined perilymphatic and intratumoral , We analyzed locoregional immunotherapy in the IL-2 injections (2/36 patients) [9], intra-arterial IL-2 guinea pig line-10 tumor model |4j. In addition to IL-2, polyethylene glycol (PEG)-modificd IL-2 was also infusion (2/12 pi 10], and combined locore gional IL-2 and LÀK cell administration (3/14 pauscd, enhancing solubility and plasma half-life [5], tients) [11], The aim of the present study was to evaluIt was found that guinea-pigs with palpable tumors ate the feasibility and the local antitumor effects of on the flank and micrometastases in the regional intratumoral PEG-IL-2 injections in HNSCC, in a lymph nodes could be cured by intratumoral, but not schedule which had been found to be optimal in our perilymphatic, injections of PEG-IL-2, whereas IL-2 animal study [4],…”
Section: Introductionmentioning
confidence: 92%
“…However, a local indurative and erythema tous reaction after subcutaneous IL-2 or PEG-IL-2 injection in humans, resembling a delayed-type hyper sensitivity reaction and consisting of mononuclear cell infiltration, has been previously described [12]. In the line-10 guinea-pig tumor, in which we previously evalu ated intratumoral PEG-IL-2 therapy [4], an intense inflammatory reaction with eosinophils, T lympho cytes, macrophages and fibroblasts was observed at the site of regressing tumors (unpublished data). A n as sociation between eosinophilia and a favorable tumor response has been described in patients receiving sub cutaneous IL-2 and IF N a therapy [13], Tepper et al, provided evidence for eosinophil-mediated tumor-cell killing in vivo [14].…”
mentioning
confidence: 93%
See 1 more Smart Citation